Errors in Writing Made by German Language Students and Suggested Solutions - misnah mannahali (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. This qualitative descriptive study aims to describe student errors in German writing and to propose solutions. The data was collected from the essays of 28 German students from the 2018 class. The results of data analysis showed that student errors in German writing varied, including 1) grammatical/structural errors in German sentences, 2) errors in conjugating German verbs that do not match the subject, 3) errors in word choices, 4) errors in prepositions, and 5) errors in the arrangement of words if there are conjunctions in the sentence. Meanwhile, the suggested solutions to these problems include the use of clustering or associograms while teaching and the development of practice materials for German writing.Keywords: Errors in Writing, German, Solution